Public perceptions of violent knife crime: a reflexive thematic analysis - Partington, Zoe; Walsh, R. Stephen; Labhardt, Danielle (Frontiers in Social Psychology, 2025)
IntroductionViolent knife crime in the UK is a complex issue, littered with ambiguities between understanding the problem and actioning impactful strategies to address it. Understanding of knife crime is complicated by inconsistent practices regarding official statistics and a lack of definition; however, social psychology may offer a means of understanding VKC that is independent from official statistics.MethodsThe current study aimed to research violent knife crime from a social identity approach (SIA) to understand the psychological structures and group processes that contribute to its continuation. Fifteen interviews were conducted with participants recruited via social media and interview transcripts were analyzed using Reflexive Thematic Analysis (RTA).ResultsFour themes were identified: (1) Views of VKC connected to stereotypes; (2) Media influence on beliefs, perceptions, and attitudes related to VKC; (3) Categorization of offenders as members of the out-group and victims as part of the in-group; and (4) The importance of multi-agency action.DiscussionThe themes were framed within a social identity approach, with reference to the social identity model of collective action. Discussions around the need for collective action toward social change are explored and a SIA informed public health approach is considered.